Clinical and economic impact of partnered pharmacist medication charting in the emergency department - Tesfay Mehari Atey; Gregory M. Peterson; Mohammed S. Salahudeen; Tom Simpson; Camille M. Boland; Ed Anderson; Barbara C. Wimmer (Frontiers Media S.A., 2023)
Introduction: Partnered pharmacist medication charting (PPMC), a process redesign hypothesised to improve medication safety and interdisciplinary collaboration, was trialed in a tertiary hospital's emergency department (ED).Objective: To evaluate the health-related impact and economic benefit of PPMC.Methods: A pragmatic, controlled study compared PPMC to usual care in the ED. PPMC included a pharmacist-documented best-possible medication history (BPMH), followed by a clinical conversation between a pharmacist and a medical officer to jointly develop a treatment plan and chart medications. Usual care included medical officer-led traditional medication charting in the ED, without a pharmacist-obtained BPMH or clinical conversation. Outcome measures, assessed after propensity score matching, were length of hospital or ED stay, relative stay index (RSI), in-hospital mortality, 30-day hospital readmissions or ED revisits, and cost.Results: A total of 309 matched pairs were analysed. The median RSI was reduced by 15.4% with PPMC (p = 0.029). There were no significant differences between the groups in the median length of ED stay (8 vs. 10 h, p = 0.52), in-hospital mortality (1.3% vs. 1.3%, p > 0.99), 30-day readmission rates (21% vs. 17%; p = 0.35) and 30-day ED revisit rates (21% vs. 19%; p = 0.68). The hospital spent approximately $138.4 for the cost of PPMC care per patient to avert at least one medication error bearing high/extreme risk. PPMC saved approximately $1269 on the average cost of each admission.Conclusion: Implementing the ED-based PPMC model was associated with a significantly reduced RSI and admission costs, but did not affect clinical outcomes, noting that there was an additional focus on medication reconciliation in the usual care group relative to current practice at our study site.